PROBLEMS AND PROSPECTS OF LEGAL STAFF TRAINING IN UZBEKISTAN (American Journal of Research in Humanities and Social Sciences, 2022)
It should be noted that every country that has chosen the path of democratic development is going to achieve high development, and it certainly needs, first of all, mature lawyers who meet international requirements, fair and humane laws. So, how are mature legal professionals being formed now? First of all, they should be highly qualified, independent-thinking legal personnel who can glorify the name of our independent Uzbekistan, what kind of nation and people the Uzbek people are to the whole world, as well as being honest, conscientious, high patriots and nationalists. Therefore, they should take the field as real defenders of our people. They should become the trust and support of our people. Then the development of the state and society will rise to high levels.